FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN SAK EMKM PADA LAPORAN KEUANGAN UMKM DI KOTA JAMBI - Amalia, Vera; Oktari, Indah Wulan (Institut Rahmaniyah Sekayu, 2023)
This study aims to examine the effect of SAK EMKM socialization and the need for bank credit on the application of SAK EMKM to MSMEs in Jambi City. This research is quantitative research with a sample size of 120 respondents. This research data was collected through questionnaires, processed and analyzed using multiple linear regression analysis. The data quality test in this research is the Pearson Correlation validity test and the reliability test using Cronbach Alpha. To test the hypothesis using the coefficient of determination test which has been adjusted to the t test and F test. The results of this research data indicate that the socialization of SAK EMKM has a positive and significant effect on the application of SAK EMKM. And banking credit needs have a positive and significant effect on the implementation of SAK EMKM